Message on Child’s Disability and Perspectives of Development: Parents’ Experiences - Ustilaitė, Stasė; Kuginytė-Arlauskienė, Ieva; Cvetkova, Leticija; Kalinkevičienė, Aušra (Pedagogika, 2015)
The article reveals experiences of parents experienced after receiving the first information on child’s disability. Data collection of qualitative phenomenological research was performed using the interview in which 12 families took part. Content analysis was applied to the data analysis. Experiences of parents reveal that professionally presented information helps a family to put up with the child’s disability providing hope for the future of the child and has the influence on family’s purposefulness, on the other hand, the information provided without using the principles of medical ethics, insensitively and unintelligibly to parents causes negative experiences. Unawareness of the true situation, lack of information on assistance resources do not create conditions for parents to become equivalent partners of specialists when providing assistance to the child. The data analysis of qualitative research reveals the need of families rearing children with disabilities for psychosocial assistance which is recognized by the informants as cooperation with specialists, families having similar experience and individual psychological support. Family counseling, the communication and cooperation of the family with various specialists and other families having similar experience is a prerequisite guaranteeing a better quality of life for children with disability and their parents.